Application of response surface methodology with a Box-Behnken design for struvite precipitation - SAYAN, PERVİZ; POLAT, SEVGİ (ELSEVIER, 2019)
Struvite crystals were precipitated by the reaction of magnesium chloride hexahydrate and ammonium dihydrogen phosphate using different concentrations of citric acid as the additive (100, 300, and 500 ppm). The structure, morphology, functional groups and particle size of the crystals were evaluated experimentally by scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and particle size analysis. The experimental results demonstrated that citric acid exerted a significant influence on the struvite precipitation and the crystal morphology changed from rod-like to tubular shaped with a larger size and hollow bodies. The average particle size changed from 17.60 to 33.60 mu m with increasing citric acid concentration. The results of FTIR suggested that the citric acid adsorbed on the crystal surface. Following the characterization of the crystals prepared using different concentrations of citric acid, the response surface methodology coupled with Box-Behnken design were applied as a statistical tool to determine the effects of the key parameters affecting the precipitation process (temperature, pH and additive concentration) on the responses (namely, particle size and specific cake resistance of struvite). Second-order polynomial equations for both responses were improved to correlate the parameters. Analysis of variance (ANOVA) showed a significant quadratic regression model with high coefficients of the determination values. The optimum conditions for particle size were found to be 60 degrees C, pH 8 and 500 ppm additive concentration. (C) 2019 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Struvite; Crystallization; Experimental design; Citric acid; Optimization; PHOSPHORUS RECOVERY; CITRIC-ACID; CRYSTALLIZATION; OPTIMIZATION; IMPACT; PARAMETERS; MORPHOLOGY; OPERATION; CALCIUM; WASTE